Deputation to Foreign Minister re Barcelona : inter-departmental correspondence - McDonald, Florence
012a-0116-001 TRADES UNION CONGRESS GENERAL COUNCIL. INTER DEPARTMENTAL CORRESPONDENCE. From F. McDonald. Department Secretary's. To: Mr. Bolton. Date 2nd April, 1938. SUBJECT. DEPUTATION TO FOREIGN MINISTER RE BARCELONA. Mr. Elvin telephoned this morning to ask whether the deputation had been fixed. I told him that we had only been able to get a few replies yesterday, but I had asked the others to 'phone by Monday morning. Mr. Elvin will be in Paris until Wednesday morning. If it is arranged for Wednesday morning he would like his home address notified by telephone, as someone from there is going down to meet him at the station on Wednesday at 9 a.m. and he could attend if the deputation is as late as Wednesday. FEM/KMS/501 292/946/12a/116(ii)